2013
DOI: 10.1371/journal.pone.0063351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induced Astigmatism on Foot Placement Strategies when Stepping onto a Raised Surface

Abstract: PurposeLarge changes in spectacle prescription can increase falls risk in older people. We investigated the effect of induced astigmatism (a common cause of distorted or blurred vision in older people) on locomotor stepping patterns to determine whether the orientation of astigmatic changes could have differential effects on gait safety when negotiating steps and stairs.Methods10 older adults (mean age 76.0±6.4 years) walked up to and stepped onto a raised block whilst wearing their spectacle prescription and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…found that, in a population of near‐emmetropic wearers (mean age 32 years), the introduction of unwanted cylindrical errors as small as 0.25 D could be detected by some individuals and that almost all wearers were dissatisfied with spectacles in which cylindrical errors were 0.50 D, with oblique errors having more deleterious effects. Changes in oblique astigmatism have also been found to be associated with increased dizziness in patients after cataract surgery, while the orientation‐dependent spectacle magnification associated with larger, particularly oblique, induced cylinder powers may cause gait and other difficulties . Nevertheless, when considering the possible acceptability of current Alvarez spectacles and their astigmatism from the point of view of safety, it must be remembered that progressive lenses, particularly those with higher additions, show very substantial amounts of astigmatism on either side of the narrow progressive corridor and that the use of such lenses, and of other forms of spectacle multifocal, is accepted, in spite of the higher rates of falls and other problems that older wearers of such lenses experience in comparison with the wear of single‐vision lenses .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that, in a population of near‐emmetropic wearers (mean age 32 years), the introduction of unwanted cylindrical errors as small as 0.25 D could be detected by some individuals and that almost all wearers were dissatisfied with spectacles in which cylindrical errors were 0.50 D, with oblique errors having more deleterious effects. Changes in oblique astigmatism have also been found to be associated with increased dizziness in patients after cataract surgery, while the orientation‐dependent spectacle magnification associated with larger, particularly oblique, induced cylinder powers may cause gait and other difficulties . Nevertheless, when considering the possible acceptability of current Alvarez spectacles and their astigmatism from the point of view of safety, it must be remembered that progressive lenses, particularly those with higher additions, show very substantial amounts of astigmatism on either side of the narrow progressive corridor and that the use of such lenses, and of other forms of spectacle multifocal, is accepted, in spite of the higher rates of falls and other problems that older wearers of such lenses experience in comparison with the wear of single‐vision lenses .…”
Section: Discussionmentioning
confidence: 99%
“…Changes in oblique astigmatism have also been found to be associated with increased dizziness in patients after cataract surgery, 33 while the orientationdependent spectacle magnification associated with larger, particularly oblique, induced cylinder powers may cause gait and other difficulties. 34 Nevertheless, when considering the possible acceptability of current Alvarez spectacles and their astigmatism from the point of view of safety, it must be remembered that progressive lenses, particularly those with higher additions, show very substantial amounts of astigmatism on either side of the narrow progressive corridor [2][3][4] and that the use of such lenses, and of other forms of spectacle multifocal, is accepted, in spite of the higher rates of falls and other problems that older wearers of such lenses experience in comparison with the wear of singlevision lenses. [35][36][37][38] The advantages of the multifocals in terms of the improvements in vision that they offer over a range of distances are judged to outweigh the disadvantages of spatial distortion and consequent accidents, and similar compromises might be justifiable in the case of the small levels of unwanted astigmatism in Alvarez lenses.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 In addition, greater changes in J 45 , the vector representing oblique astigmatism, were a risk factor for post-operative dizziness (OR 5.2, Table 3). This is not surprising given that astigmatic correction can lead to distortions in how patients perceive in 3-D space 47,48 and oblique astigmatism is known to produce the greatest problems of distortion 25 and difficulties in adaptation. 36 The strong link between post-operative falls rate and dizziness symptoms (OR, 3.17, p = 0.002) was expected and has been suggested by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…14,22 • Adaptation problems to large changes in refractive correction. 23 These include spectacle magnification and astigmatic distortion changes increasing trip risk on steps and stairs 24,25 and requiring adaptation of the vestibulo-ocular reflex gain. Patients can complain of their visual world appearing to 'swim' until adaptation occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The FI increased significantly from C+4.00 D in the condition of 180° on the right eye/90° on the left eye, C+3.00 D in 45° on the right eye/135° on the left eye, from C+3.00 D in 45° on both eyes compared to that under corrected emmetropia. Johnson et al 23 ) investigated the effect of induced astigmatism on locomotor stepping patterns in subjects blurred with ±3.00 D cylinders at axes of 180°, 90°, 135° and 45°; they reported obliquely induced astigmatism causes more gait changes than vertically and horizontally induced astigmatism despite similar visual acuity levels with the addition of all cylindrical lenses. Moreover, Chapman et al 24 ) investigated the effects of ocular magnification on adaptive gait with size lenses producing ocular magnification of ±1%, ±2%, ±3%, and ±5%; they suggest the observed adaptive gait changes are driven by magnification changes rather than optical blurring.…”
Section: Discussionmentioning
confidence: 99%